PE#01 Price escalation for plumbing pipes and electricity cable works rev.02 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of revised price escalation quotation for plumbing pipes and electricity cable works of BRACU new campus project.